A waterproof PET film for photovoltaic backsheet and preparation method thereof
By combining modified PET, modified talc and functionalized polysiloxane, a waterproof PET film with excellent flame retardancy, anti-aging properties and self-repairability was prepared, which solved the problem of insufficient performance of existing photovoltaic backplane materials and significantly improved its performance and life in harsh environments.
Patent Information
- Application Number
- CN202510029533.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
AI Technical Summary
Existing photovoltaic backplane materials cannot meet the requirements of excellent flame retardancy and anti-aging performance, and it is difficult to effectively protect solar cells in harsh environments.
Modified PET, modified talc powder and functionalized polysiloxane were mixed with electrospinning and stacked into a film, and immersed in perfluorooctyl ethylene solution to prepare a waterproof PET film. The film forms a thermally reversible crosslinking network through the reaction of amino groups and chlorine, introducing phosphorus elements and silicon oxygen long chains to improve flame retardancy, mechanical properties and self-healing properties.
The excellent flame retardancy, anti-aging performance and self-repair performance of the waterproof PET film used in the photovoltaic backplane are achieved, which significantly improves its service life and performance stability in harsh environments.
Smart Images

Figure SMS_8 
Figure SMS_9 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic backboards, and in particular to a waterproof PET film for photovoltaic backboards and a preparation method thereof. Background Art
[0002] With the progress of photoelectric conversion technology of crystalline silicon solar cells, solar cell power generation technology with environmental protection and energy saving advantages has been widely used and promoted, thereby driving a huge market demand for solar cell backplanes. The photovoltaic backplane is located on the back of the photovoltaic module, supporting the battery, and can also protect the solar cell from interference from the harsh external environment, ensuring the normal operation of the photovoltaic module, thereby extending the service life of the photovoltaic module. Polymer film materials with a single performance advantage cannot meet the performance requirements of solar cell backplanes. Therefore, the present invention prepares a waterproof PET film for photovoltaic backplanes with excellent flame retardancy and anti-aging properties. Summary of the invention
[0003] The object of the present invention is to provide a waterproof PET film for photovoltaic backboard and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses a waterproof PET film for a photovoltaic backboard. The waterproof PET film for a photovoltaic backboard is prepared by mixing modified PET, modified talcum powder and functionalized polysiloxane, electrostatically spinning and depositing the mixture into a film, and then immersing the mixture in a perfluorooctylethylene solution.
[0005] As an optimization, the modified PET is obtained by alcoholyzing PET powder with ethylene glycol and then copolymerizing it with 4,4'-dithiodibenzoic acid and a flame retardant monomer.
[0006] As an optimization, the PET powder comes from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0007] As an optimization, the flame retardant monomer is obtained by reacting diethyl chloromethylphosphonate and N-(5-aminopentyl)maleimide.
[0008] As an optimization, the modified talc is obtained by reacting talc with 3-aminopropyltrimethoxysilane and then grafting 2-hydroxy-5-methylisophthalaldehyde and 2,5-bis(aminomethyl)furan.
[0009] As an optimization, the talcum powder model is 325 mesh and comes from Linyang Mineral Products Processing Plant in Lingshou County.
[0010] As an optimization, the functionalized polysiloxane is obtained by reacting 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and hexamethyldisiloxane.
[0011] A method for preparing a waterproof PET film for a photovoltaic backplane comprises the following preparation steps: (1) Mix talcum powder and 70% to 80% ethanol solution in a mass ratio of 1:(55 to 65), perform ultrasonic dispersion for 25 to 35 min, add 3-aminopropyltrimethoxysilane (0.09 to 0.11 times the mass of talcum powder), stir at 65 to 75 °C and 100 to 200 rpm for 1 to 3 h, rotary evaporate at 50 to 60 °C for 1 to 2 h, dry at 55 to 65 °C for 23 to 25 h, grind and sieve through 150 to 250 mesh to obtain pre-modified Pre-modified talc; pre-modified talc, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol are mixed in a mass ratio of 1:(1.7-1.9):(1.1-1.2):(25-35), stirred in a nitrogen atmosphere at 45-55° C. and 200-300 rpm for 4-6 hours, naturally cooled to room temperature and then filtered, washed with deionized water for 3-5 times, and dried at 65-75° C. for 8-10 hours to obtain modified talc; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1:(1-3):(0.01-0.03), stirred at 85-95°C and 100-200 rpm for 2-3 hours in a nitrogen atmosphere, hexamethyldisiloxane (0.2-0.4 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) is added, the temperature is raised to 95-105°C and stirring is continued for 7-9 hours, the temperature is raised to 130-140°C at a rate of 10-20°C / min and stirring is continued for 40-50 minutes, and distilled at 0.1-0.3 MPa for 1-2 hours to obtain functionalized polysiloxane; (3) Mix diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide in a mass ratio of 1:(1.2-1.4):(5-7), stir at 75-85°C and 100-300 rpm for 10-12 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol 3-5 times, and dry at 65-75°C for 11-13 hours to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:(0.01-0.03):(5-7), stirred at 190-200°C and 100-200 r / min for 3-5 h, filtered while hot, cooled naturally to room temperature, washed with deionized water for 3-5 times, and dried at 65-75°C for 8-10 h to obtain alcoholysed PET; alcoholysed PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:(0.6-0. 8):(0.7~0.8):(0.01~0.03) mix well, stir in nitrogen atmosphere, 105~115℃, 100~200r / min for 20~40min, heat to 260~270℃, -0.15~-0.05MPa, 110~130r / min and continue stirring for 45~55min, heat to 275~285℃, 45~55Pa, 90~110r / min and stir for 1~2h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:(0.04-0.06):(0.1-0.3), and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 125-135°C for 8-10 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 1-3 minutes, taken out and hung to air-dry until no liquid dripped within 5-15 seconds, and allowed to stand at 80-90°C for 8-10 hours to obtain a waterproof PET film for photovoltaic backplane.
[0012] As an optimization, the reaction equation of the pre-modified talc in step (1) is: .
[0013] As an optimization, the reaction equation of the modified talc in step (1) is: .
[0014] As an optimization, the reaction equation of the functionalized polysiloxane in step (2) is: .
[0015] As an optimization, the reaction equation of the flame retardant monomer in step (3) is: .
[0016] As an optimization, the reaction equation for alcoholysis of PET in step (4) is: .
[0017] As an optimization, the reaction equation of the modified PET in step (4) is: ; Where R is .
[0018] As an optimization, the calendering film forming parameters in step (5) are: temperature 125°C, heating time 10s, setting time 15s, pressure 10MPa, and film thickness 80μm.
[0019] As an optimization, the perfluorooctylethylene solution in step (5) is obtained by mixing perfluorooctylethylene, chloroplatinic acid and methanol in a mass ratio of 1:0.01:9.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing a waterproof PET film for a photovoltaic backboard, the present invention comprises the following steps: reacting talc powder with 3-aminopropyltrimethoxysilane, grafting 2-hydroxy-5-methylisophthalaldehyde and 2,5-bis(aminomethyl)furan to obtain modified talc powder; reacting 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and hexamethyldisiloxane to obtain functionalized polysiloxane; reacting diethyl chloromethylphosphonate with N-(5-aminopentyl)maleimide to obtain a flame retardant monomer; alcoholyzing the PET powder with ethylene glycol, and then copolymerizing with 4,4'-dithiodibenzoic acid and the flame retardant monomer to obtain a modified PET; uniformly mixing the modified PET, the modified talc powder and the functionalized polysiloxane, rolling the mixture into a film, and then immersing the mixture in a perfluorooctylethylene solution to obtain a waterproof PET film for a photovoltaic backboard.
[0021] Firstly, talc was reacted with 3-aminopropyltrimethoxysilane, and then grafted with 2-hydroxy-5-methylisophthalaldehyde and 2,5-bis(aminomethyl)furan to obtain modified talc. 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and hexamethyldisiloxane were reacted to obtain functionalized polysiloxane. Through the polymerization of amino and aldehyde groups, long chains containing furan structures were grafted on the surface of talc, and DA reaction was carried out with maleimide on the main chain of PET to form a thermally reversible cross-linked network, thereby improving the self-repairing performance of waterproof PET film used for photovoltaic backplane. The phenol structure on 2-hydroxy-5-methylisophthalaldehyde can form a hydrogen bonded six-membered ring with the Schiff base structure, absorb ultraviolet light and convert it into heat energy, and capture free radicals to prevent the oxidation reaction, thereby improving the anti-aging performance of the waterproof PET film used for photovoltaic backplanes. Polysiloxanes containing pyrrole rings and silicon-hydrogen bonds are synthesized by hydrolysis and condensation, and long silicon-oxygen chains that can form a dense silicon-carbon layer during the combustion process are introduced. At the same time, the thermally reversible cross-linking network of the DA reaction is enriched, thereby further improving the flame retardancy, mechanical properties and self-healing properties of the waterproof PET film used for photovoltaic backplanes.
[0022] Secondly, diethyl chloromethylphosphonate and N-(5-aminopentyl)maleimide are reacted to obtain a flame retardant monomer; PET powder is hydrolyzed with ethylene glycol and then copolymerized with 4,4'-dithiodibenzoic acid and a flame retardant monomer to obtain a modified PET; the modified PET, modified talc and functionalized polysiloxane are mixed and rolled into a film, and then immersed in a perfluorooctylethylene solution to obtain a waterproof PET film for photovoltaic backplanes; maleimide structure is grafted onto diethyl chloromethylphosphonate by utilizing the reaction of amino and chlorine, and then connected to the PET main chain by ester exchange, and phosphorus element is introduced to form a protective layer which decomposes at the combustion temperature, thereby improving the waterproofness of the photovoltaic backplane. The flame retardant properties of water-resistant PET film are improved; at the same time, maleimide can undergo cycloaddition with furan and pyrrole to form a thermally reversible cross-linking network, thereby improving the mechanical properties and self-healing properties of the waterproof PET film used for photovoltaic backplanes; 4,4'-dithiodibenzoic acid is used as a chain extender to polymerize with PET after alcoholysis to introduce low-energy disulfide bonds, which can break at room temperature and combine with their own sulfur atoms to improve the self-healing properties of the waterproof PET film used for photovoltaic backplanes; through the hydrosilylation reaction, perfluorooctylethylene is used to trim the surface of the film to form a protective layer, thereby improving the waterproofness of the waterproof PET film used for photovoltaic backplanes. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Mix talcum powder and 70% ethanol solution in a mass ratio of 1:55, ultrasonically disperse for 25 minutes, add 3-aminopropyltrimethoxysilane (0.09 times the mass of talcum powder), stir at 65°C and 100 rpm for 3 hours, rotary evaporate at 50°C for 2 hours, dry at 55°C for 25 hours, grind and sieve 150 mesh to obtain pre-modified talcum powder; mix pre-modified talcum powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol in a mass ratio of 1:1.7:1.1:25, stir at 45°C and 200 rpm for 6 hours in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with deionized water three times, and dry at 65°C for 10 hours to obtain modified talcum powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:1:0.01, stirred at 85°C and 100 rpm for 3 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.2 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 95°C and stirring was continued for 9 h, the temperature was raised to 130°C at a rate of 10°C / min and stirring was continued for 50 min, and distilled at 0.1 MPa for 2 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.2:5, stirred at 75°C and 100 rpm for 12 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol three times, and dried at 65°C for 13 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.01:5, stirred at 190°C and 100 r / min for 5 h, filtered while hot, naturally cooled to room temperature, washed with deionized water for 3 times, and dried at 65°C for 10 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.6:0.7:0.01, stirred in a nitrogen atmosphere at 105°C and 100 r / min for 40 min, heated to 260°C, -0.15 MPa, 110 r / min, and continued to stir for 55 min, heated to 275°C, 45 Pa, and 90 r / min for 2 h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.04:0.1, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 125°C for 10 h to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 1 min, taken out and hung to air until no liquid dripped within 5 s, and allowed to stand at 80°C for 10 h to obtain a waterproof PET film for photovoltaic backplane.
[0025] A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed in a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved through 200 mesh to obtain pre-modified talc powder; pre-modified talc powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol were mixed in a mass ratio of 1:1.8:1.15:30, stirred at 50 ° C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 70 ° C for 9 h to obtain modified talc powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:2:0.02, stirred at 90°C and 150 rpm for 2.5 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.3 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 h, the temperature was raised to 135°C at a rate of 15°C / min and stirring was continued for 45 min, and distilled at 0.2 MPa for 1.5 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.3:6, stirred at 80°C and 200 rpm for 11 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 12 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.7:0.75:0.02, stirred in a nitrogen atmosphere at 110°C and 150 r / min for 30 min, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.05:0.2, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 130°C for 9 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 2 minutes, taken out and hung to air until no liquid dripped within 10 seconds, and allowed to stand at 85°C for 9 hours to obtain a waterproof PET film for photovoltaic backplane.
[0026] A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Mix talcum powder and 80% ethanol solution in a mass ratio of 1:65, ultrasonically disperse for 35 minutes, add 3-aminopropyltrimethoxysilane (0.11 times the mass of talcum powder), stir at 75°C and 200 rpm for 1 hour, rotary evaporate at 60°C for 1 hour, dry at 65°C for 23 hours, grind and sieve through 250 mesh to obtain pre-modified talcum powder; mix pre-modified talcum powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol in a mass ratio of 1:1.9:1.2:35, stir at 55°C and 300 rpm for 4 hours in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with deionized water 5 times, and dry at 75°C for 8 hours to obtain modified talcum powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:3:0.03, stirred at 95°C and 200 rpm for 2 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.4 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 105°C and stirring was continued for 7 h, the temperature was raised to 140°C at a rate of 20°C / min and stirring was continued for 40 min, and distilled at 0.3 MPa for 1 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.4:7, stirred at 85°C and 300 rpm for 10 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 5 times, and dried at 75°C for 11 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.03:7, stirred at 200°C and 200 r / min for 3 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 5 times, and dried at 75°C for 8 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.8:0.8:0.03, stirred in a nitrogen atmosphere at 115°C and 200 r / min for 20 min, heated to 270°C, -0.05 MPa, 130 r / min, and continued to stir for 45 min, heated to 285°C, 55 Pa, and 110 r / min for 1 h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.06:0.3, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 135°C for 8 h to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 3 min, taken out and hung to air-dry until no liquid dripped within 15 s, and allowed to stand at 90°C for 8 h to obtain a waterproof PET film for photovoltaic backplane.
[0027] Comparative Example 1: A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed at a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved to 200 mesh, to obtain pre-modified talc powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:2:0.02, stirred at 90°C and 150 rpm for 2.5 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.3 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 h, the temperature was raised to 135°C at a rate of 15°C / min and stirring was continued for 45 min, and distilled at 0.2 MPa for 1.5 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.3:6, stirred at 80°C and 200 rpm for 11 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 12 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.7:0.75:0.02, stirred in a nitrogen atmosphere at 110°C and 150 r / min for 30 min, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (5) The modified PET, pre-modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.05:0.2, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 130°C for 9 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 2 minutes, taken out and hung to air until no liquid dripped within 10 seconds, and allowed to stand at 85°C for 9 hours to obtain a waterproof PET film for photovoltaic backplane.
[0028] Comparative Example 2: A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed in a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved through 200 mesh to obtain pre-modified talc powder; pre-modified talc powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol were mixed in a mass ratio of 1:1.8:1.15:30, stirred at 50 ° C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 70 ° C for 9 h to obtain modified talc powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:2:0.02, stirred at 90°C and 150 rpm for 2.5 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.3 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 h, the temperature was raised to 135°C at a rate of 15°C / min and stirring was continued for 45 min, and distilled at 0.2 MPa for 1.5 h to obtain functionalized polysiloxane; (3) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid and antimony trioxide were mixed in a mass ratio of 1:1.4:0.02, stirred at 110°C and 150 r / min for 30 min in a nitrogen atmosphere, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (4) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.05:0.2, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 130°C for 9 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 2 minutes, taken out and hung to air until no liquid dripped within 10 seconds, and allowed to stand at 85°C for 9 hours to obtain a waterproof PET film for photovoltaic backplane.
[0029] Comparative Example 3: A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed in a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved through 200 mesh to obtain pre-modified talc powder; pre-modified talc powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol were mixed in a mass ratio of 1:1.8:1.15:30, stirred at 50 ° C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 70 ° C for 9 h to obtain modified talc powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:2:0.02, stirred at 90°C and 150 rpm for 2.5 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.3 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 h, the temperature was raised to 135°C at a rate of 15°C / min and stirring was continued for 45 min, and distilled at 0.2 MPa for 1.5 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.3:6, stirred at 80°C and 200 rpm for 11 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 12 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:1.5:0.02, stirred at 110°C and 150 r / min for 30 min in a nitrogen atmosphere, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.05:0.2, and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 130°C for 9 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 2 minutes, taken out and hung to air until no liquid dripped within 10 seconds, and allowed to stand at 85°C for 9 hours to obtain a waterproof PET film for photovoltaic backplane.
[0030] Comparative Example 4: A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed in a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved through 200 mesh to obtain pre-modified talc powder; pre-modified talc powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol were mixed in a mass ratio of 1:1.8:1.15:30, stirred at 50 ° C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 70 ° C for 9 h to obtain modified talc powder; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:2:0.02, stirred at 90°C and 150 rpm for 2.5 h in a nitrogen atmosphere, and hexamethyldisiloxane (0.3 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 h, the temperature was raised to 135°C at a rate of 15°C / min and stirring was continued for 45 min, and distilled at 0.2 MPa for 1.5 h to obtain functionalized polysiloxane; (3) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.3:6, stirred at 80°C and 200 rpm for 11 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 12 h to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.7:0.75:0.02, stirred in a nitrogen atmosphere at 110°C and 150 r / min for 30 min, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:0.05:0.2, rolled into a film using a flat vulcanizer, and allowed to stand at 130°C for 9 hours to obtain a waterproof PET film for photovoltaic backplanes.
[0031] Comparative Example 5: A method for preparing a waterproof PET film for a photovoltaic backsheet, the method for preparing a waterproof PET film for a photovoltaic backsheet comprising the following preparation steps: (1) Talc powder and 75% ethanol solution were mixed in a mass ratio of 1:60, ultrasonically dispersed for 30 min, 3-aminopropyltrimethoxysilane (0.1 times the mass of talc powder) was added, stirred at 70 ° C and 150 rpm for 2 h, rotary evaporated at 55 ° C for 1.5 h, dried at 60 ° C for 24 h, ground and sieved through 200 mesh to obtain pre-modified talc powder; pre-modified talc powder, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol were mixed in a mass ratio of 1:1.8:1.15:30, stirred at 50 ° C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 70 ° C for 9 h to obtain modified talc powder; (2) Diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide were mixed in a mass ratio of 1:1.3:6, stirred at 80°C and 200 rpm for 11 h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 12 h to obtain a flame retardant monomer; (3) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:0.02:6, stirred at 195°C and 150 r / min for 4 h, filtered while hot, naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 9 h to obtain alcoholysis PET; alcoholysis PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:0.7:0.75:0.02, stirred in a nitrogen atmosphere at 110°C and 150 r / min for 30 min, heated to 265°C, -0.1 MPa, 120 r / min, and continued to stir for 50 min, heated to 280°C, 50 Pa, and 100 r / min, and stirred for 1.5 h to obtain modified PET; (4) The modified PET and modified talc were mixed in a mass ratio of 1:0.05, rolled into a film using a flat vulcanizer, and allowed to stand at 130°C for 9 hours to obtain a pre-modified PET film; the pre-modified PET film was immersed in a perfluorooctylethylene solution for 2 minutes, taken out and hung to air until no liquid dripped within 10 seconds, and allowed to stand at 85°C for 9 hours to obtain a waterproof PET film for photovoltaic backplane.
[0032] Test Example 1: 1. Waterproof Test method: The waterproof PET film for photovoltaic backsheet obtained in each embodiment and the comparative example were taken to have the same size, and the hydrostatic pressure resistance was measured using a digital water permeability tester (YG812L Laizhou Electronic Instrument).
[0033] 2. Flame retardant properties Test method: The waterproof PET film for photovoltaic backsheet obtained in each embodiment and the comparative example were taken with the same size to test the limiting oxygen index.
[0034] Table 1 below shows the analysis results of the flame retardant and waterproof properties of the waterproof PET films used for photovoltaic backsheets using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0035] Table 1 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the waterproof PET film for photovoltaic backsheet prepared by the present invention has good flame retardant and waterproof properties.
[0036] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which indicates that the maleimide structure is grafted onto diethyl chloromethylphosphonate by reacting amino groups with chlorine, and then connected to the PET main chain by ester exchange, thereby introducing phosphorus elements that decompose at combustion temperature to form a protective layer, thereby improving the flame retardant properties of the waterproof PET film used for photovoltaic backplanes.
[0037] By comparison, the hydrostatic pressure of Examples 1, 2, and 3 is higher than that of Comparative Example 4, which indicates that the surface of the film is treated with perfluorooctylethylene through the hydrosilylation reaction to form a protective layer, thereby improving the waterproofness of the waterproof PET film used for the photovoltaic backplane.
[0038] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 5, which indicates that the polysiloxane containing pyrrole rings and silicon-hydrogen bonds is synthesized by hydrolysis and condensation, and the long silicon-oxygen chains that can form a dense silicon-carbon layer during the combustion process are introduced, thereby improving the flame retardancy of the waterproof PET film used for photovoltaic backplanes.
[0039] Test Example 2: 1. Mechanical properties Test method: The waterproof PET film for photovoltaic backsheet obtained in each embodiment and the comparative example are cut into standard dumbbell-shaped samples of the same size, and the tensile strength σ0 is tested according to the national standard GB / T1040.
[0040] 2. Anti-aging Test method: Take the same standard dumbbell-shaped samples of the waterproof PET film for photovoltaic backplane obtained in each embodiment and the control example, use an aging test box, age for 1 day at 70°C, 1W / m2, 340nm, measure the tensile strength σ1, and calculate the aging rate = (σ0-σ1) / σ0×100%.
[0041] 3. Self-healing Test method: Take the same standard dumbbell-shaped samples of the waterproof PET film for photovoltaic backsheet obtained in each embodiment and the comparative example, cut them in the middle, place the cut surfaces in close contact at 60°C for 24 hours, measure the tensile strength σ2, and calculate the high-temperature repair rate = σ2 / σ0×100%.
[0042] Table 2 below shows the analysis results of the anti-aging, self-repairing and mechanical properties of the waterproof PET films used for photovoltaic backsheets using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0043] Table 2 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the waterproof PET film for photovoltaic backsheet prepared by the present invention has good anti-aging, self-repairing and mechanical properties.
[0044] By comparison, compared with Example 1, Examples 1, 2, and 3, the tensile strength and repair rate are higher and the aging rate is lower, which indicates that through the polymerization of amino and aldehyde groups, a long chain containing a furan structure is grafted on the surface of talcum powder, and a DA reaction is carried out with the maleimide on the PET main chain to form a thermally reversible cross-linked network, thereby improving the self-healing performance and mechanical properties of the waterproof PET film used for photovoltaic backplanes; the phenol structure on the 2-hydroxy-5-methylisophthalaldehyde can form a hydrogen bond hexacyclic ring with the Schiff base structure to absorb ultraviolet light and convert it into heat energy, and can also capture free radicals to prevent the oxidation reaction from proceeding, thereby improving the anti-aging performance of the waterproof PET film used for photovoltaic backplanes.
[0045] By comparison, the tensile strength and repair rate of Examples 1, 2, and 3 are higher than those of Comparative Example 2, which illustrates that the maleimide structure is grafted on diethyl chloromethylphosphonate by reacting amino groups and chlorine, and then connected to the PET main chain through ester exchange. The grafted maleimide can undergo cycloaddition with furan and pyrrole to form a thermally reversible cross-linked network, thereby improving the mechanical properties and self-healing properties of the waterproof PET film used for photovoltaic backplanes.
[0046] By comparison, the repair rates of Examples 1, 2, and 3 are higher than that of Comparative Example 3, indicating that 4,4'-dithiodibenzoic acid is used as a chain extender to polymerize with PET after alcoholysis, and low-energy disulfide bonds are introduced, which can be combined with their own sulfur atoms while breaking at room temperature, thereby improving the self-healing property of the waterproof PET film used for photovoltaic backplanes.
[0047] By comparison, Examples 1, 2, and 3 have higher tensile strength and repair rate than Comparative Example 5, indicating that the polysiloxane containing pyrrole rings and silicon-hydrogen bonds is synthesized by hydrolysis and condensation to enrich the thermally reversible cross-linking network of the DA reaction and further improve the mechanical properties and self-healing properties of the waterproof PET film used for photovoltaic backplanes.
[0048] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A waterproof PET film for photovoltaic backsheet, characterized in that: The waterproof PET film for photovoltaic backplane is prepared by mixing modified PET, modified talc and functionalized polysiloxane, rolling them into a film, and then immersing them in a perfluorooctylethylene solution; The modified PET is obtained by alcoholyzing PET powder with ethylene glycol and then copolymerizing it with 4,4'-dithiodibenzoic acid and a flame retardant monomer; The flame retardant monomer is obtained by reacting diethyl chloromethylphosphonate and N-(5-aminopentyl)maleimide; The modified talc is obtained by reacting talc with 3-aminopropyltrimethoxysilane and grafting 2-hydroxy-5-methylisophthalaldehyde and 2,5-bis(aminomethyl)furan. The functionalized polysiloxane is obtained by reacting 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and hexamethyldisiloxane.
2. A method for preparing a waterproof PET film for a photovoltaic backsheet, characterized in that: The method comprises the following preparation steps: (1) Mix talcum powder and 70% to 80% ethanol solution in a mass ratio of 1:(55 to 65), perform ultrasonic dispersion for 25 to 35 min, add 3-aminopropyltrimethoxysilane (0.09 to 0.11 times the mass of talcum powder), stir at 65 to 75 °C and 100 to 200 rpm for 1 to 3 h, rotary evaporate at 50 to 60 °C for 1 to 2 h, dry at 55 to 65 °C for 23 to 25 h, grind and sieve through 150 to 250 mesh to obtain pre-modified Pre-modified talc; pre-modified talc, 2-hydroxy-5-methylisophthalaldehyde, 2,5-bis(aminomethyl)furan and anhydrous ethanol are mixed in a mass ratio of 1:(1.7-1.9):(1.1-1.2):(25-35), stirred in a nitrogen atmosphere at 45-55° C. and 200-300 rpm for 4-6 hours, naturally cooled to room temperature and then filtered, washed with deionized water for 3-5 times, and dried at 65-75° C. for 8-10 hours to obtain modified talc; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, N-(3-trimethoxysilylpropyl)pyrrole and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1:(1-3):(0.01-0.03), stirred at 85-95°C and 100-200 rpm for 2-3 hours in a nitrogen atmosphere, hexamethyldisiloxane (0.2-0.4 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) is added, the temperature is raised to 95-105°C and stirring is continued for 7-9 hours, the temperature is raised to 130-140°C at a rate of 10-20°C / min and stirring is continued for 40-50 minutes, and distilled at 0.1-0.3 MPa for 1-2 hours to obtain functionalized polysiloxane; (3) Mix diethyl chloromethylphosphonate, N-(5-aminopentyl)maleimide and dimethyl sulfoxide in a mass ratio of 1:(1.2-1.4):(5-7), stir at 75-85°C and 100-300 rpm for 10-12 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol 3-5 times, and dry at 65-75°C for 11-13 hours to obtain a flame retardant monomer; (4) PET powder, zinc acetate dihydrate and ethylene glycol were mixed in a mass ratio of 1:(0.01-0.03):(5-7), stirred at 190-200°C and 100-200 r / min for 3-5 h, filtered while hot, cooled naturally to room temperature, washed with deionized water for 3-5 times, and dried at 65-75°C for 8-10 h to obtain alcoholysed PET; alcoholysed PET, 4,4'-dithiodibenzoic acid, flame retardant monomer and antimony trioxide were mixed in a mass ratio of 1:(0.6-0. 8):(0.7~0.8):(0.01~0.03) mix well, stir in nitrogen atmosphere, 105~115℃, 100~200r / min for 20~40min, heat to 260~270℃, -0.15~-0.05MPa, 110~130r / min and continue stirring for 45~55min, heat to 275~285℃, 45~55Pa, 90~110r / min and stir for 1~2h to obtain modified PET; (5) The modified PET, modified talc and functionalized polysiloxane were mixed in a mass ratio of 1:(0.04-0.06):(0.1-0.3), and the film was rolled into a film using a flat vulcanizer. The film was allowed to stand at 125-135°C for 8-10 hours to obtain a pre-modified PET film. The pre-modified PET film was immersed in a perfluorooctylethylene solution for 1-3 minutes, taken out and hung to air-dry until no liquid dripped within 5-15 seconds, and allowed to stand at 80-90°C for 8-10 hours to obtain a waterproof PET film for photovoltaic backplane.
3. The method for preparing a waterproof PET film for a photovoltaic backsheet according to claim 2, characterized in that: The reaction equation of the pre-modified talcum powder in step (1) is: 。 4. The method for preparing a waterproof PET film for a photovoltaic backsheet according to claim 2, characterized in that: The reaction equation of the modified talcum powder in step (1) is: 。 5. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The reaction equation of the functionalized polysiloxane in step (2) is: 。 6. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The reaction equation of the flame retardant monomer in step (3) is: 。 7. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The reaction equation for alcoholysis of PET in step (4) is: 。 8. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The reaction equation of the modified PET in step (4) is: ; Where R is: 。 9. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The calendering film forming parameters in step (5) are: temperature 125° C., heating time 10 s, setting time 15 s, pressure 10 MPa, and film thickness 80 μm.
10. The method for preparing a waterproof PET film for a photovoltaic back sheet according to claim 2, characterized in that: The perfluorooctylethylene solution in step (5) is obtained by mixing perfluorooctylethylene, chloroplatinic acid and methanol in a mass ratio of 1:0.01:9.
Citation Information
Cited By
Degradable packaging material and preparation method thereof
CN120424457A
A biodegradable packaging material and its preparation method
CN120424457B
Hydrophilic-hydrophobic double-sided synchronous processing device and method for solar photovoltaic backboard
CN121815793A